Pirolisis Tandan Kosong Sawit Menjadi Bio-Oil Menggunakan Katalis Mo/NZA - Firman Syah; Syaiful Bahri; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Fuel oil is a very important requirement in life. The fuel used for this comes from crude oil extracted from the ground, while fuel oil is non-renewable, so for the next few years is expected the public will experience a shortage of fuel. So, we need alternative energy instead of petroleum. Biomass can be used as bio-oil by pyrolysis. Biomass using such as empty fruit bunches oil. Empty Fruit Bunch Oil is organic waste that has the potential to be used as asubstitute fuel bioenergy, the largest waste generated by oil palm plantations. The purpose of this study is to produce bio-oil from empty fruit bunches of oil using catalysts Mo/NZA the pyrolysis process, as well as determine the effect of the ratio of the catalyst of biomass empty fruit bunches of oil to the yield of bio-oil produced from empty fruit bunches of oil and determine the characteristics of the chemical and physical properties of bio -oil produced from oil palm empty fruit bunches. In this research Empty Fruit Bunch Oil by the size of - 100+200 mesh, 50 grams, 500 ml silinap and catalyst Mo/NZA inserted into of pyrolysis reactor. This process conducted at a temperature 320oC and the stirring speed of 300 rpm operate for about 120 minutes by flowing nitrogen gas. For the optimum yields obtained at 1.5% catalyst Mo/NZA as much as 5% of biomass that is equal to 56.28%. The test results physical properties obtained density of 1.005 g/ml, 2,296 cSt viscosity, acidity 45,373 mg NaOH /g sample and the flash point 52oC. Respectively the characterization of the chemical properties of bio - oil using Gas Chromatography - Mass Spectroscopy (GC - MS) obtained some dominant chemical components such as:: (Pentane, 2,2,4,4-tetramethyl-), (1-Pentene, 2.4 , 4-trimethyl-), (Cyclohexane, 1-bromo-4-methyl), (Hexane, 2,2-dimethyl-), (Pentane, 2,4- dimethyl-).Keywords: bio-oil, biomass, catalyst mo / NZA, oil palm empty fruit bunches